The effects of organic and mineral fertilizers on carbon sequestration, soil properties, and crop yields from a long‐term field experiment under a Swiss conventional farming system. (14th March 2018) - Maltas, Alexandra; Kebli, Hedi; Oberholzer, Hans Rudolf; Weisskopf, Peter; Sinaj, Sokrat
Abstract: The effects of mineral fertilizers and organic amendments on soil properties, carbon (C) sequestration, and crop yields are studied in a 37‐year field experiment, Phosphorus–Potassium‐balanced design, in Switzerland. Treatments included a control (mineral fertilization) without nitrogen (N) fertilizers ( Min‐N0 ) and with optimal N ( Min‐Nopt) and 5 organic amendments (green manure [ Gm ], cereal straw [ Str ], fresh cattle manure in 2 doses 35 and 70 t ha −1 [ Ma35 and Ma70 ] and cattle slurry [ Slu ]) all receiving the same optimal N fertilization as Min‐Nopt . All mineral and organic treatments received optimum P–K fertilization. Nitrogen fertilization ( Min‐Nopt vs. Min‐N0 ) increased soil organic C, microbial activity, and microporosity but decreased pH, magnesium, and macroporosity. All organic treatments with optimal mineral N resulted in higher soil organic C content compared with Min‐Nopt, however, these effects were significant only for the highest dose of manure. The organic amendments supplied 25% to 80% additional C input to the soil compared with Min‐Nopt, and their amendment‐C retention coefficients ranged from 1.6% ( Gm ) to 13.6% ( Ma70 ). Chemical, physical, and biological soil properties were not or slightly significantly different among organic treatments. Nevertheless, soils fertilized with farmyard manure produced generally higher grain yield (up to 7.3%) compared with Min‐Nopt whereas the opposite effect was noted for Gm (−2.2%) and Str (−5.2%) treatments due to their negative effect on N availability. In conclusion, Gm and Str treatments were as effectives as Ma35 and Slu treatments to prevent soil degradation but required higher chemical fertilizer to maintain crop yield.